2014
DOI: 10.1073/pnas.1324021111
|View full text |Cite
|
Sign up to set email alerts
|

Shigella IpaH7.8 E3 ubiquitin ligase targets glomulin and activates inflammasomes to demolish macrophages

Abstract: When nucleotide-binding oligomerization domain-like receptors (NLRs) sense cytosolic-invading bacteria, they induce the formation of inflammasomes and initiate an innate immune response. In quiescent cells, inflammasome activity is tightly regulated to prevent excess inflammation and cell death. Many bacterial pathogens provoke inflammasome activity and induce inflammatory responses, including cell death, by delivering type III secreted effectors, the rod component flagellin, and toxins. Recent studies indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 57 publications
6
97
0
Order By: Relevance
“…Shigella species target GLMN by translocation of an E3 ligase (invasion plasmid antigen H7.8) into host cells; IpaH7.8 ubiquitinates GLMN, resulting in its degradation at the proteasome and relieving its inhibition of an unidentified Cullin ring ligase. 45 This study provides indirect evidence that activity of a Cullin ring ligase may be important for NLRP3 activation, and proposes that ubiquitination provides a non-degradative, activating stimulus for the NLRP3 inflammasome.…”
Section: Nlrp3: Ubiquitinationmentioning
confidence: 84%
“…Shigella species target GLMN by translocation of an E3 ligase (invasion plasmid antigen H7.8) into host cells; IpaH7.8 ubiquitinates GLMN, resulting in its degradation at the proteasome and relieving its inhibition of an unidentified Cullin ring ligase. 45 This study provides indirect evidence that activity of a Cullin ring ligase may be important for NLRP3 activation, and proposes that ubiquitination provides a non-degradative, activating stimulus for the NLRP3 inflammasome.…”
Section: Nlrp3: Ubiquitinationmentioning
confidence: 84%
“…[103][104][105] Another NEL effector, IpaH7.8, possesses E3 ligase activity in vitro and targets an inhibitor of Cullin-based RING E3 ligase named GLMN for degradation, which augments inflammasome activation. 106 In addition, OspG and OspI, belonging to a different subsets of S. flexneri effectors, have recently been identified to suppress NF-κB activation by disrupting the ubiquitin system. Mammalian serine/threonine kinase imitator OspG binds to many ubiquitinated E2 proteins, including UbcH5 and Ubch7, in host cells, thereby enhancing its own kinase activity and preventing the ubiquitination and degradation of phosphorylated IκBα.…”
Section: Shigella Flexnerimentioning
confidence: 99%
“…The mechanism by which IpaH7.8 induced macrophage cell death is via IpaH7.8 E3 ligasemediated proteasome-dependent GLMN degradation in a cell model of BMDMs and peritoneal macrophages isolated from BALB/c mice. GLMN is polyubiquitinated in the presence of IpaH7.8 [139]. In this context, Wang et al, showed that the production and secretion of IpaH4.5 by Shigella interacts with p65 inhibiting the transcriptional activity of NF-κB through the NTR domain of IpaH4.5 and the p65 region spanning from amino acids 1-190.…”
Section: • • Inflammation Induced By Eiecmentioning
confidence: 99%